Tingkat Dekomposisi Bahan Organik pada Sedimen di Tukad Daya Desa Bungkulan Kabupaten Buleleng, Provinsi Bali - Dresti Ngurah Dwi Saputra; Ima Yudha Perwira; Alfi Hermawati Waskita Sari (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
The purpose of this study were to know decomposition rate in the sediment, the ratio of C/N, and the supporting parameters (Ammonia, Nitrate and pH) in the sediment in Daya River. Sediment samples were taken from 6 points in Daya River by purposive sampling. Sediment samples were analyzed for organic carbon, total nitrogen, total bacterial number, ammonia, nitrate, and pH. The results showed that organic carbon content in the sediment was 27.96%, total nitrogen content was 1.12%, and total bacterial number was 7.1 x105 CFU/ml. Based on this result, the C/N ratio is around 28.71 indicating balance condition of decomposition. The average value of ammonia, nitrate and pH were: were 1.21 mg/L, 0.92 mg/L, 7.39, respectively. The supporting parameters in Daya River are pH and Nitrate in the sediment in Tukad Daya in optimal conditions to support the decomposition of organic matter in Daya River. Ammonia in the sediment in Daya River exceeds the optimal limit for living organisms during the decomposition process of organic matter.